Effects of Near-Peer Motivational Interviewing Teaching on Greek Medical Students - George Zhou; Ilina Sohal; Josna Jose; Athanasia Sandali; Evangelia Savvidou; Emmanouil Smyrnakis (University Library System, University of Pittsburgh, 2023)
BACKGROUND: Obesity presents as a significant and increasingly prevalent public health problem globally. Greece reported an adult obesity rate of 17% in 2016 (OECD) and a more alarming paediatric overweight/obesity rate of 1 in 3 children (WHO). However, weight management can be difficult to negotiate and implement successfully with patients. Previous studies have reported positive results when utilising Motivational Interviewing (MI) techniques in these consultations. To ensure that healthcare systems are well-equipped to deal with increasing obesity rates, it is important to develop MI skills in medical students. Near-peer teaching has been reported as an effective method to improve student learning, and a gap in the literature exists regarding this type of teaching initiative for MI skills. AIM: To introduce and assess the effects of near-peer MI teaching, with the focus on weight management, on the knowledge and skills of medical students with limited previous exposure to the topic. To evaluate and compare how different methods of delivering near-peer teaching material between in-person and online sessions affect teaching efficacy. METHODS: An interactive seminar was delivered in English/Greek, both in-person and online, for Aristotle University of Thessaloniki (AUTh) students in years 3-6 and year 6 respectively. Materials were adapted to the local context from curriculum and literature, and delivered by final year AUTh and KCL medical students based at AUTh. Each seminar consisted of a theoretical section and a practical section. First, a teaching sheet was handed out to the participants that accompanied a PowerPoint presentation. The latter included information on MI for the Overweight/Obese Population, as well as demonstration video clips on certain concepts. Following the presentation, participants were split into small groups to apply MI in a Role-Playing environment. Scenarios were handed out and practiced by two participants in each group, as well as Examiners' checklists for the observers. This process was repeated three times with different scenarios and participants, and each turn was followed by a short discussion to provide feedback. Anonymous pre- and post-teaching evaluation surveys were also distributed and returned immediately before and after teaching with both cohorts. RESULTS: There were 88 total participants, with 10 in the in-person and 78 in the online cohort. A significant improvement (p<0.001) was seen for both in-person and online cohorts in 5-point Likert confidence ratings for using MI skills whilst consulting both simulated (95%CI, i-p[1.83,3.37];o[1.64,2.05]) and real (95%CI, i-p[1.71,3.09];o[1.56,2.00]) overweight/obese patients. The in-person cohort showed greater positive change across all question domains assessing confidence on session content compared to the online cohort, beginning with skills such as motivational interviewing. CONCLUSION: Near-peer education is an effective method to improve medical student confidence in MI skills, and suggests the potential success of a long-term student-led clinical communication skills course run alongside the core curriculum.